Doing ethnographies - Crang, Mike (SAGE, 2007)
Doing Ethnographies is an introductory and applied guide to ethnographic methods. It focuses on those methods - participant observation, interviewing, focus groups, and video/photographic work - that allow us to understand the lived, everyday world. Informed by the authors' fieldwork experience, the book covers the relation between theory, practice and writing, and demonstrates how methods work in the field, so preparing the first-time ethnographer for the loss of control and direction often experienced.